A Study of Post-Impressionism in Ukrainian Painting of the 20th Century - Pavlova, Tetyana (HUDPROM: The Ukrainian Art and Design Journal, 2023)
A Study of Post-Impressionism in Ukrainian Painting of the 20th Century